VD_FINDINFO HC / 2009 / 203 vom 2. Juni 2009 - VD Tribunal cantonal (2009)
SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE, SURSIS À L'EXÉCUTION DE LA PEINE | 42 ch. 1 CP, 42 CP, 43 ch. 1 CP, 411 let. j CPP, 415 CPP